The Ontology of Vision. The Invisible, Consciousness of Living Matter - Fiorio, Giorgia (Frontiers in Psychology, 2016)
If I close my eyes, the absence of light activates the peripheral cells devoted to the perception of darkness. The awareness of “seeing oneself seeing” is in its essence a thought, one that is internal to the vision and previous to any object of sight. To this amphibious faculty, the “diaphanous color of darkness,” Aristotle assigns the principle of knowledge. “Vision is a whole perceptual system, not a channel of sense.” Functions of vision are interwoven with the texture of human interaction within a terrestrial environment that is in turn contained into the cosmic order. A transitive host within the resonance of an inner-outer environment, the human being is the contact-term between two orders of scale, both bigger and smaller than the individual unity. In the perceptual integrative system of human vision, the convergence-divergence of the corporeal presence and the diffraction of its own appearance is the margin. The sensation of being no longer coincides with the breath of life, it does not seems “real” without the trace of some visible evidence and its simultaneous “sharing”. Without a shadow, without an imprint, the numeric copia of the physical presence inhabits the transient memory of our electronic prostheses. A rudimentary “visuality” replaces tangible experience dissipating its meaning and the awareness of being alive. Transversal to the civilizations of the ancient world, through different orders of function and status, the anthropomorphic “figuration” of archaic sculpture addressees the margin between Being and Non-Being. Statuary human archetypes are not meant to be visible, but to exist as vehicles of transcendence to outlive the definition of human space-time. The awareness of individual finiteness seals the compulsion to “give body” to an invisible apparition shaping the figuration of an ontogenetic expression of human consciousness. Subject and object, the term “humanum” fathoms the relationship between matter and its living dimension, “this de facto vision and the ‘there is’ which it contains.” The project reconsiders the dialectic between the terms vision–presence in the contemporary perception of archaic human statuary according to the transcendent meaning of its immaterial legacy.